2005
DOI: 10.4028/www.scientific.net/msf.500-501.677
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Strain Induced Precipitation of Nb in Microalloyed Austenite Using Classical and Novel Techniques

Abstract: In this contribution strain induced precipitation of niobium carbides has been analyzed making use of different hot-rolling simulators and combining the advanced precipitation characterization methods of selective chemical extraction and transmission electron microscopy. A laboratory cast Fe-0.1C-0.07Nb alloy has been employed for the study. Thermomechanical simulations were carried out by torsion, plastodilatometry and plane strain compression techniques. The results have shown that, in spite of the different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 15 publications
1
12
0
Order By: Relevance
“…To the authors knowledge, very few data is available on the comparison of the recrystallized fraction obtained from different simulation techniques. Only Iparraguirre et al 26 compared softening fractions obtained from plastodilatometry and from torsion, showing a difference in softening level between both types of tests. In spite of these differences, they found a relatively good correlation in the measurements of the precipitate size and the amount of Nb precipitated in the different types of experiments.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To the authors knowledge, very few data is available on the comparison of the recrystallized fraction obtained from different simulation techniques. Only Iparraguirre et al 26 compared softening fractions obtained from plastodilatometry and from torsion, showing a difference in softening level between both types of tests. In spite of these differences, they found a relatively good correlation in the measurements of the precipitate size and the amount of Nb precipitated in the different types of experiments.…”
Section: Resultsmentioning
confidence: 99%
“…So far, only few comparisons between different techniques and methods were reported. Iparraguirre et al 26 studied the differences in recrystallization behavior by double deformation testing using different mechanical testing modes, i.e. uniaxial compression on a dilatometer and torsion tests.…”
Section: Introductionmentioning
confidence: 99%
“…In some cases precipitates are detected on replicas before the onset of precipitation is defined by the "plateau" in the softening curve. 41,42) On the other hand, difficulties arise in separating the hardness increment owing to the precipitates from other mechanisms, such as grain size strengthening, solid solution strengthening and dislocation strengthening. 30) It has been found that microhardness measurements lead to longer periods than in chemical analysis for strain-induced precipitation measurements.…”
Section: Precipitation Constantsmentioning
confidence: 99%
“…This is reasonable taking into account previous experiences relative to the size of precipitates found at initial stages of strain induced precipitation. [27][28][29] In the same figure the F PIN corresponding to a nitrogen content of 40 ppm has been included for comparison, since this value is within the typical range of industrial eutectoid steel grades without specific nitrogen addition. The reduction in nitrogen from 110 to 40 ppm shifts the precipitation start temperature of VN in austenite to significantly lower temperatures, reducing almost completely the possibility of interaction between recrystallization and precipitation during practical rolling.…”
Section: )mentioning
confidence: 99%
“…27) and between 14 and 27 % in Ref. 28) for Nb(C, N) precipitation. It must be taken into account that in the present study precipitation was analyzed after the last pass, i.e.…”
Section: Austenite Conditioningmentioning
confidence: 99%